Pressure-Induced Superconductivity In Polycrystalline La_{3}Ni_{2}O_{7-δ} - G. Wang; N. N. Wang; X. L. Shen; J. Hou; L. Ma; L. F. Shi; Z. A. Ren; Y. D. Gu; H. M. Ma; P. T. Yang; Z. Y. Liu; H. Z. Guo; et al. (Physical Review X, 2024)
We synthesized polycrystalline La_{3}Ni_{2}O_{7−δ} (δ≈0.07) samples by using the sol-gel method without postannealing under high oxygen pressure, and then measured temperature-dependent resistivity under various hydrostatic pressures up to 18 GPa by using the cubic anvil and two-stage multianvil apparatus. We find that the density-wave-like anomaly in resistivity is progressively suppressed with increasing pressure and the resistivity drop corresponding to the onset of superconductivity emerges at pressure as low as ∼6  GPa. Zero resistivity is achieved at 9 GPa below T_{c}^{zero}≈6.6  K, which increases quickly with pressure to 41 K at 18 GPa. However, the diamagnetic response was not detected in the ac magnetic susceptibility measurements up to 15 GPa, indicating a filamentary nature of the observed superconductivity in the studied pressure range. The constructed T-P phase diagram reveals an intimate relationship between superconductivity, density-wave-like order, and the strange-metal-like behaviors. The observation of zero-resistance state in the polycrystalline La_{3}Ni_{2}O_{7−δ} samples under high pressures not only corroborates the recent report of superconductivity in the pressurized La_{3}Ni_{2}O_{7} crystals but also facilitates further studies on this emerging family of nickelate high-T_{c} superconductors.